Determinant actions in men`s professional padel performance - Romeroa, G.; González-Silva, J.; Conejero, M.; Fernández-Echeverría, C. (International Journal of Performance Analysis in Sport, 2024)
The main objective of the present research was to know the variables of the game in padel determining in the sport performance in men`s category in the season 2022-2023 in World Padel Tour. The independent variables considered in this study were: court side, laterality, stroke type, origin of the ball, net distance, shot direction and trajectory. The dependent variable was the effectiveness of the game actions. Four thousand five hundred and five game actions were analysed during the finals of the four masters (Marbella, Valladolid, Madrid, Buenos Aires) and the final master (Barcelona) of the 2022-2023 season of the World Padel Tour were analysed. The multinomial logistic regression applied showed that, the variables that predict the effectiveness of the game actions are: stroke type, net distance, shot direction and trajectory (level of statistical significance was p < .05). Specifically, our results show us that the stroke type that we must use to be more effective and score points is the smash, we must hit down the line, from areas close to the net and with a downward trajectory. These results show the characteristics of the game actions that determine the performance with the aim that they can help guide coaches in the training process of padel players.